Implementasi Pembiayaan ProdukAmanah Berdasarkan Fatwa DSN-MUI No.92/DSN-MUI/IV/2014 Pada PT Pegadaian Syariah Cabang Cinere - Mega Nopiantisisar,; Mira Rahmi,; Lili Puspita Sari, (2021)
The existence of Islamic financial institutions plays an important role when providing options for financial service needs from various economic fields. Islamic financial institutions are financial service institutions that market financial products and services that are in line with sharia principles, therefore they must be selective in implementing sharia-compliant products and free from gharar and usury. One of the financial institutions (non-bank) that is free from gharar and usury is the Sharia Pawnshop. This Sharia pawnshop is based on avoiding old tactics such as bonded tactics, loan sharks, and inhumane loans. Pegadain Syariah has a fairly exclusive product, namely Amanah Products. The purpose of this study is to analyze and prove the implementation of a trust financing product based on the DSN-MUI Fatwa at PT Pegadaian Syariah Cinere Branch. This type of research is descriptive qualitative research. Data were collected by conducting interviews, observations, and documentation. And data analysis includes three processes, namely data reduction, data presentation and conclusion drawing. The result of this research is the financing of trust products at PT Pegadaian Syariah Cinere Branch using 2 contracts, namely murabahah and rahn contracts. The suitability of the fatwa related to financing accompanied by rahn with the financing of this trust product is in accordance with existing provisions such as those related to general provisions, legal provisions, collateral (marhun), debt (marhun bih), income (murtahin), settlement (contract rahn) and disputes.